The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2020.587492
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of FGF21, β-Klotho, and BDNF in Stable Coronary Artery Disease Patients With Depressive Symptoms: A Cross-Sectional Single-Center Study

Abstract: Background: The incidence of depressive symptoms (DS) in patients with stable coronary artery disease (SCAD) is significantly higher than those in healthy population, and that DS are independent risk factors for cardiovascular events. Previous studies have reported that fibroblast growth factor 21 (FGF21), β-klotho, mature brain-derived neurotrophic factor (mBDNF), and BDNF precursor (proBDNF) play important roles in the pathogenesis and treatment of coronary heart disease and depression. With this in mind, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
(26 reference statements)
0
15
0
3
Order By: Relevance
“…They have been confirmed to have a high probability to be concomitant and to have an adverse effect on each other, pushing patients to undertake heavier burdens and suffering when they are afflicted by these diseases concurrently (Whooley et al, 2008 ). On the one hand, patients with CHD are more likely to suffer from mental disorders because they usually endure unpleasant symptoms like angina without warning and are required to take several kinds of medications for their whole life, resulting in negative emotions like anxiety or depression (Colquhoun et al, 2013 ; Wu et al, 2021 ). To be concrete, 20–30% of patients with heart diseases are diagnosed with anxiety or depression (Larsen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…They have been confirmed to have a high probability to be concomitant and to have an adverse effect on each other, pushing patients to undertake heavier burdens and suffering when they are afflicted by these diseases concurrently (Whooley et al, 2008 ). On the one hand, patients with CHD are more likely to suffer from mental disorders because they usually endure unpleasant symptoms like angina without warning and are required to take several kinds of medications for their whole life, resulting in negative emotions like anxiety or depression (Colquhoun et al, 2013 ; Wu et al, 2021 ). To be concrete, 20–30% of patients with heart diseases are diagnosed with anxiety or depression (Larsen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sigma-1 receptor agonists such as endogenous neurosteroid dehydroepiandosterone (DHEA) and selective serotonin reuptake inhibitors (SSRIs) have shown potent cardio-protective and antidepressant effects. In this study, Wu et al ( 4 ) firstly found that serum β-klotho in the depression group was significantly reduced, and that β-klotho was negatively correlated with the depression score. However, the detailed mechanisms remain to be identified.…”
mentioning
confidence: 75%
“…However, the detailed mechanisms remain to be identified. Also, Wu et al ( 4 ) found that serum mBDNF levels were decreased in SCAD patients, and that mBDNF level and mBDNF/proBDNF ratio in the depression group were significantly decreased. More importantly, serum mBDNF levels were negatively correlated with SDS score.…”
mentioning
confidence: 97%
See 2 more Smart Citations